Research on Intelligent Monitoring of Urban Environment under the Environment of the Internet of Things - Wang, Pengyu (E3S web of conferences, 2023)
With the development of the economy, human society has gradually strengthened the emphasis on environmental protection. Environmental monitoring, early warning, and governance have become important worldwide tasks. Traditional urban environmental monitoring relies on environmental monitoring stations. Manual data collection, processing, and analysis often consume a lot of manpower, and at the same time, efficiency and accuracy are lacking. The Internet of Things and sensors enable people to carry out unmanned collection, transmission, and analysis. This paper discusses the research on intelligent monitoring of the urban environment under the Internet of Things, designs the scheme from the software and hardware perspective, and proposes a time series data prediction method based on the Gaussian process. It is hoped that this article can provide some references for applying the collected massive environmental data.